Review of Lypusinae (Lepidoptera: Gelechioidea: Lypusidae) from Korea with a description of a new species of Agnoea Walsingham, 1907 - Sohn, Jae-Cheon; Lvovsky, Alexander L. (Zootaxa, 2021)
The subfamily Lypusinae of Korea is reviewed with three species including a new species, Agnoea danguni Sohn, sp. nov. belonging to nominotypical subgenus, and two species of Agnoea belonging to the subgenus Tubuliferodes Toll, 1956: A. (T.) digitiella Kim, 2020 and A. (T.) josephinae (Toll, 1956). The female characters of A. digitiella are described for the first time. Additional collecting records are provided for A. digitiella and A. josephinae. Photographs of the habitus and the genitalia are provided for all three species of Agnoea known so far from Korea.